Adolescentes filhos de dependentes químicos em abstinência: Como se relacionam com o álcool? - Podolano, Andréia Arend (Universidade do Vale do Rio dos Sinos, 2019)
The consumption of psychoactive substances draws attention as it grows and awakens the increasingly interesting interest of adolescents, which usually start with the use of alcohol. It is known that the family has an important role, both as a protective factor and of risk for the use of substances, as well as recognizing the issue of transgenerational transmission of chemical dependence. Thus, children of chemical addicts are more susceptible to alcohol use and abuse. However, it is questioned what the relationship of adolescent children with alcohol is when the parents, dependent on the chemical, are abstinent. This dissertation aims to evaluate the relationship of adolescents with alcohol in families in which at least one of the parents is a chemical dependent on abstinence. The dissertation document consists of two empirical articles, both of qualitative character. In the first, performed with four adolescents, it evaluates how the children perceive the pattern of alcohol consumption of the parents and the consequences of this use for their lives. In the second, it is verified the contrasting relationship of two adolescents with alcohol, regarding situations of exposure, experimentation, use and/or abuse, family and social demands. The results indicate that despite the adolescents know the risks that are due to being children of chemical dependents, even if in abstinence, the characteristics of this phase of development cause it to debridge ambivalence regarding the use of alcohol. In this sense, the adaptation of the family to the adolescent phase, the style of communication and autonomy given to the children were determinant for the use or not of alcohol. It is evident the need for attention to the risk of substance abuse by the children, even in the context of abstinence from the parents, being important the monitoring of adolescent behavior.
Keywords: Famílias dependentes químicas; Abstinência; Filhos adolescentes; Ambivalência; Uso de álcool; Chemical dependent families; Abstinence; Adolescent children; Ambivalence; Alcohol use; ACCNPQ::Ciências Humanas::Psicologia